2021
DOI: 10.1136/bmjopen-2020-047645
|View full text |Cite
|
Sign up to set email alerts
|

Modified effect of active or passive smoking on the association between age and abdominal aortic calcification: a nationally representative cross-sectional study

Abstract: ObjectiveThe deleterious effects of smoking on atherosclerosis were well known; however, the interaction among ageing, smoking and atherosclerosis remains unclear. This study tested the hypothesis that the association between age and vascular calcification, a critical mark of atherosclerosis, was modified by smoking.DesignCross-sectional study.SettingA nationally representative sample, the National Health and Nutrition Examination Surveys 2013–2014.ParticipantsThis study included 3140 adults aged 40–80 years wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…After smoking, hypoxia and hypercapnia cause a rapid increase in erythrocyte volume, and a large number of aggregated platelets increase blood viscosity and affect blood circulation. Increased smoking can increase the risk of vascular embolism and vascular crisis in the free flap 25 . Simultaneously, smoking can increase nitric oxide (NO) in the blood, and NO can competitively bind to hemoglobin, decreasing blood oxygen 26 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After smoking, hypoxia and hypercapnia cause a rapid increase in erythrocyte volume, and a large number of aggregated platelets increase blood viscosity and affect blood circulation. Increased smoking can increase the risk of vascular embolism and vascular crisis in the free flap 25 . Simultaneously, smoking can increase nitric oxide (NO) in the blood, and NO can competitively bind to hemoglobin, decreasing blood oxygen 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased smoking can increase the risk of vascular embolism and vascular crisis in the free flap. 25 Simultaneously, smoking can increase nitric oxide (NO) in the blood, and NO can competitively bind to hemoglobin, decreasing blood oxygen. 26 Mlodinow 7 found that a long smoking history significantly increases the risk of flap necrosis after mastectomy.…”
Section: Smoking Has a Negative Prognosis For Flapsmentioning
confidence: 99%
“…A systematic review summarized that biological sex has important effects on the risk of VC [31], and Wu et al speculated that biological sex-related differences in VC probability could result from differential expression or levels of vitamin D, anti-calcific molecules (matrix Gla protein), soluble klotho, and other hormones (parathyroid hormone, fibroblast growth factor-23, and sclerostin). Noxious environmental stimuli, such as active and passive smoking [32], cadmium exposure [33], and air pollution [34] have also been suggested as modifiers of the probability of VC worsening. Dietary fiber content has also been found to modulate the risk of VC development and worsening among those with CKD [35].…”
Section: Vc Heterogeneity: Potential Originsmentioning
confidence: 99%
“…Moreover, smoking cessation has been shown to reduce the deleterious effects of smoking on abdominal aortic atherosclerosis. [111][112][113] In the CARDIA study, The AAC score was an early indicator of atherosclerosis as it reflects atherosclerotic CVD when CAC is zero. 114 The prevalence of AAC was 53% among young adults, 114 and AAC scores were generally found to be higher than CAC scores.…”
Section: Early Determinants Of Cardiovascular Disease Compendiummentioning
confidence: 99%